A randomized controlled trial with bright light and melatonin for delayed sleep phase disorder: Effects on subjective and objective sleep. (February 2014) - Saxvig, Ingvild West; Wilhelmsen-Langeland, Ane; Pallesen, Ståle; Vedaa, Øystein; Nordhus, Inger Hilde; Bjorvatn, Bjørn
<x xml:space="preserve">Abstract</x> Delayed sleep phase disorder (DSPD) is assumed to be common amongst adolescents, with potentially severe consequences in terms of school attendance and daytime functioning. The most common treatment approaches for DSPD are based on the administration of bright light and/or exogenous melatonin with or without adjunct behavioural instructions. Much is generally known about the chronobiological effects of light and melatonin. However, placebo-controlled treatment studies for DSPD are scarce, in particular in adolescents and young adults, and no standardized guidelines exist regarding treatment. The aim of the present study was, therefore, to investigate the short- and long-term effects on sleep of a DSPD treatment protocol involving administration of timed bright light and melatonin alongside gradual advancement of rise time in adolescents and young adults with DSPD in a randomized controlled trial and an open label follow-up study. A total of 40 adolescents and young adults (age range 16–25 years) diagnosed with DSPD were recruited to participate in the study. The participants were randomized to receive treatment for two weeks in one of four treatment conditions: dim light and placebo capsules, bright light and placebo capsules, dim light and melatonin capsules or bright light and melatonin capsules. In a follow-up study, participants were re-randomized to either receive treatment with the combination of bright light and melatonin or no treatment in an open label trial for approximately three months. Light and capsules were administered alongside gradual advancement of rise times. The main end points were sleep as assessed by sleep diaries and actigraphy recordings and circadian phase as assessed by salivary dim light melatonin onset (DLMO). During the two-week intervention, the timing of sleep and DLMO was advanced in all treatment conditions as seen by about 1 h advance of bed time, 2 h advance of rise time and 2 h advance of DLMO in all four groups. Sleep duration was reduced with approximately 1 h. At three-month follow-up, only the treatment group had maintained an advanced sleep phase. Sleep duration had returned to baseline levels in both groups. In conclusion, gradual advancement of rise time produced a phase advance during the two-week intervention, irrespective of treatment condition. Termination of treatment caused relapse into delayed sleep times, whereas long-term treatment with bright light and melatonin (three months) allowed maintenance of the advanced sleep phase.